Concerns about climate change among rural residents in Australia. (April 2020) - Austin, Emma K.; Rich, Jane L.; Kiem, Anthony S.; Handley, Tonelle; Perkins, David; Kelly, Brian J.
Abstract: Climate change impacts human health and there is growing recognition of the explicit consequences for mental health and wellbeing. Rural communities are recognised as one of the most vulnerable populations to climate change. The majority of research to date is quantitative and has a focus on farmers specifically, with the impacts of climate change on the wider rural community considered to a lesser extent. Our study addresses this gap by analyzing qualitative data from the Australian Rural Mental Health Study (ARMHS), a longitudinal study conducted in non-metropolitan New South Wales (NSW), Australia, during the Millennium Drought. Free text responses from 823 participants to the open-ended question "What is your biggest concern about climate change?" were analysed to determine what the qualitative data from ARMHS reveals about the mental health and wellbeing of rural communities. Four themes were identified: (i) suffering under climate change; (ii) causes of climate change; (iii) extremes of climate change; and (iv) leadership and action to address climate change. The environmental, financial, health and social impacts of climate change were of greatest concern to rural residents. Many participants also had concerns relating to climate change attribution, with many believing climate change was a natural, cyclical process not caused by human actions. Other major concerns were the financial consequences of extreme events and the adequate communication of climate change information. Analysis of qualitative data such as that presented here gives context and breadth of understanding to issues identified via quantitative analysis. Importantly, insights emerging from qualitative data, and the personal/community context that is not always available from quantitative data, can lead to more informed community-based approaches to addressing climate change issues experienced by vulnerable populations. Highlights: First population-based study to ask rural residents about climate change concerns. Qualitative analysis offers perspective of those most vulnerable to climate change. Rural residents are concerned about the financial burden of extreme weather events. Rural residents are concerned about government policies related to climate change. Many rural residents' concerns relate to the causes of climate change.